2008
DOI: 10.1002/masy.200850407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blending Factors on Eri Silk and Cotton Blended Yarn and Fabric Characteristics

Abstract: Summary: Eri cocoons were prepared into short fibers and subsequently blended with cotton fiber in order to develop the new fiber blended yarn in the short spinning system. The Eri and cotton fibers were blended using the drawframe blending with varying blending factors, viz. blending composition (0-100%) and yarn counts (30 and 50 tex). The results showed that Eri fiber which was longer and stronger than cotton fiber, affected the fiber distribution in the yarn cross-section. The mechanical properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Effect of bleaching on the physical properties of the blended yarns From the previous results [10], the physical properties of the blended yarn after peroxide bleaching were varied depending on the fibre blend ratios. Because of the different fibre lengths, finenesses and strengths between Eri silk and cotton, their fibre distribution at different ratios provided different physical properties [8,16]. In this study, the colour (L* and whiteness) ( Figure 1) and mechanical properties ( Figure 2) of the blended yarn after bleaching under different conditions were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of bleaching on the physical properties of the blended yarns From the previous results [10], the physical properties of the blended yarn after peroxide bleaching were varied depending on the fibre blend ratios. Because of the different fibre lengths, finenesses and strengths between Eri silk and cotton, their fibre distribution at different ratios provided different physical properties [8,16]. In this study, the colour (L* and whiteness) ( Figure 1) and mechanical properties ( Figure 2) of the blended yarn after bleaching under different conditions were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Society of Dyers and Colourists blended fibres were spun into yarn with a linear density of 50 tex using the ring spinning method according to our previous study [8].…”
Section: Coloration Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan detaylı incelemelerde ipek liflerinin iç giysilerde kullanılmasına dair kapsamlı bir çalışmaya rastlanamamıştır. Araştırmacılar, daha çok ipek liflerinin eğrilmesi konusuna odaklanmışlardır [11][12][13][14][15][16][17][18] ısıl temas özellikleri ıslak ve kuru şartlarda incelenmiştir. İlk temas anındaki ısıl özellikler üzerinde şardonlama işleminin, iplik tipi ve lif karışımından daha önemli olduğunu vurgulamışlardır [22].…”
Section: Introductionunclassified
“…The stress-elongation behavior of mulberry and non-mulberry silk fibers have been compared by Kothari et al [17]. Chollakup et al have studied the effect of blending eri silk with cotton fibers and found that the tensile properties of the woven fabrics were improved with the increase in silk content [18]. In this study, we have chosen muga, eri and their blend silk fabrics for possible combination with leather for making various life style products including clothing.…”
Section: Introductionmentioning
confidence: 99%